Authoritarian Parenting Styles and Social Behaviours of French Students in the Universities in Ekiti State (British Journal of Multidisciplinary and Advanced Studies, 2025)
The paper examined authoritarian parenting styles and social behaviour of French Students in the Universities in Ekiti State. Descriptive research design of the survey type was adopted for the study. The population for the study consisted of all adolescents French Students in three Universities in Ekiti State. 200 adolescent French Students were selected from three Universities in Ekiti State. 50 were selected through simple random sampling technique from each of the Universities. Data collected were analysed using both descriptive (frequencies and percentages) and inferential (Spearman rank and Pearson correlation) statistics. The study revealed that, the majority of parents of adolescent French Students in the three Universities use authoritative parenting style. Again, most of the French Students in the Universities selected have high social development. There was a weak positive non-significant relationship between parenting styles and cooperation of the students (r = 0.260, sig= 0.000).There was a weak negative significant relationship between parenting style and humility of the students (r = 0.008, sig r = 0.910). There was a significant difference between authoritarian parenting style and empathy of the students (r = 0.126, significant relationship 0.076) lastly, there was a significant difference between authoritarian parenting style and peer group (r = 0.157*, sig r = 0026) It was recommended among others that, parents in the district are educated through District Assembly policies and programmes on the importance and influence of their parenting styles. Also, the local government chiefs, parents, and teachers should put in measures to ensure the continuous and optimum social development of Secondary School Students.